Analisis Faktor Kesulitan Belajar Matematika Siswa Kelas III SDN Keroncong Mas Permai - Wahyuni Desti Utami; Aam Amaliyah; Moh. Zamroni (Journal on Education, 2023)
This study aims to describe the factors of learning difficulties in mathematics for third grade students. This research is a descriptive qualitative research by taking data at SDN Keroncong Mas Permai with the subjects and objects of research are students and homeroom teachers. Data collection techniques were carried out by observation, interviews, tests and documentation. Data analysis was collected by collecting data, reducing data, presenting data, and drawing conclusions. The result of this research is that there are several third grade students at SDN Keroncong Mas Permai who have difficulty learning mathematics. Students' mathematics learning difficulties are caused by two factors, namely internal factors and external factors. Internal factors are factors that come from the students themselves such as student attitudes, motivation in students, body health and students' sensing abilities. While external factors are factors that come from outside students such as school facilities, teachers, infrastructure, family environment, and community environment.